2006
DOI: 10.1128/aac.00131-06
|View full text |Cite
|
Sign up to set email alerts
|

The Cfr rRNA Methyltransferase Confers Resistance to Phenicols, Lincosamides, Oxazolidinones, Pleuromutilins, and Streptogramin A Antibiotics

Abstract: A novel multidrug resistance phenotype mediated by the Cfr rRNA methyltransferase is observed in Staphylococcus aureus and Escherichia coli. The cfr gene has previously been identified as a phenicol and lincosamide resistance gene on plasmids isolated from Staphylococcus spp. of animal origin and recently shown to encode a methyltransferase that modifies 23S rRNA at A2503. Antimicrobial susceptibility testing shows that S. aureus and E. coli strains expressing the cfr gene exhibit elevated MICs to a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
382
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 617 publications
(404 citation statements)
references
References 27 publications
2
382
1
8
Order By: Relevance
“…Methylation of the C8 position of A2503 in S. aureus by the Cfr enzyme leads to multidrug resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins, and streptogramin A (PhLOPS A ) (26,66,67). The A2503 nucleotide interacts with linezolid and is ∼98% conserved throughout all kingdoms (52); nevertheless, it can be modified without interfering with protein biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of the C8 position of A2503 in S. aureus by the Cfr enzyme leads to multidrug resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins, and streptogramin A (PhLOPS A ) (26,66,67). The A2503 nucleotide interacts with linezolid and is ∼98% conserved throughout all kingdoms (52); nevertheless, it can be modified without interfering with protein biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The rRNA methyltransferase coded by the cfr gene modifies the adenine residue at position 2503 of the 23S rRNA, resulting in resistance to antibiotics including lincosamides, phenicols, pleuromutilins and streptogramin A (Long et al, 2006). Among the 14 cfr-positive isolates, 12, 11 and 10 isolates exhibited altered resistance to erythromycin, chloramphenicol and clindamycin, respectively, whereas all isolates were susceptible to vancomycin and teicoplanin.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, exposures to antibiotics that acted on the bacterial ribosome were pooled together in the risk analysis because of a recent study that identified a plasmid-mediated transferable rRNA methyltransferase in Staphylococcus aureus. 26 Although this has not been identified in Enterococcus species, the transfer of other genetic material between these 2 bacteria has been described.…”
Section: Discussionmentioning
confidence: 99%